Quantitative review of ecosystem services and disservices studies in the tropics (2019)
The tropics host about 80% of the planet’s terrestrial species and over 95% of its corals. A well-known tropical forest ecosystem to provide significant global regulating services has declined at a rate of 5.5 M ha per year from 1990-2015, while another region noted an increase per year. There is evidence that tropical region ecosystem services and disservices are the least studied in the world. This study quantified peer-review papers in the tropics, then explored the neglected ecosystem type, service category, assessment mode, applied techniques and choice dependence between ecosystem type, service category, assessment mode and applied techniques. The Google Scholar and Web of Science database were used to collect all ES & ED studies available online from 1960 to December 2017. This review covered 102 countries with 578 articles. The study showed dramatic articles increase in the last three years as more than 50% of articles were published after the year of 2014. The top countries in high articles were Mexico (n = 53), India (n = 43), and Brazil (n = 35). The ES & ED assessment tools/techniques are barely applied in tropics as only social based techniques such as interviews and questionnaire take over 45%, while biophysical tools like remote sensing and GIS appeared only in 20%, InVEST only in 3% while the rest tools are less than 1% even none such as ARIES model. Urban and marine ecosystem types, disservices category and trade-off assessment mode were the least studied. The review concluded that policy analysis ES & ED studies do not reflect the trade-offs and synergy analysis between different services which hinder the development of pragmatic policy and decisions toward ES sustainable management in the tropics. The rampant urbanization in the tropics is subjected to destroy existing ES. Thus, this review highly suggested a high concern of urbanization ecosystem. This study also calls for great academic research to give attention to the tropical rainforest region as most African countries to host such forest have not even a single article on ES & ED.